Pilot Study of Delayed ICOS/ICOS-L Blockade With αCD40 to Modulate Pathogenic Alloimmunity in a Primate Cardiac Allograft Model. Issue 2 (February 2018) - O'Neill, Natalie A.; Zhang, Tianshu; Braileanu, Gheorghe; Cheng, Xiangfei; Hershfeld, Alena; Sun, Wenji; Reimann, Keith A.; Dahi, Sia; Kubicki, Natalia; Hassanein, Wessam; Laird, Christopher; Cimeno, Arielle; et al.
Abstract : Background: Inducible costimulator (ICOS) is rapidly upregulated with T-cell stimulation and may represent an escape pathway for T-cell costimulation in the setting of CD40/CD154 costimulation blockade. Induction treatment exhibited no efficacy in a primate renal allograft model, but rodent transplant models suggest that the addition of delayed ICOS/ICOS-L blockade may prolong allograft survival and prevent chronic rejection. Here, we ask whether ICOS-Ig treatment, timed to anticipate ICOS upregulation, prolongs NHP cardiac allograft survival or attenuates pathogenic alloimmunity. Methods: Cynomolgus monkey heterotopic cardiac allograft recipients were treated with αCD40 (2C10R4, d0-90) either alone or with the addition of delayed ICOS-Ig (d63-110). Results: Median allograft survival was similar between ICOS-Ig + αCD40 (120 days, 120-125 days) and αCD40 (124 days, 89-178 days) treated animals, and delayed ICOS-Ig treatment did not prevent allograft rejection in animals with complete CD40 receptor coverage. Although CD4 + TEM cells were decreased in peripheral blood (115 ± 24) and mLNs (49 ± 1.9%) during ICOS-Ig treatment compared with monotherapy (214 ± 27%, P = 0.01; 72 ± 9.9%, P = 0.01, respectively), acute and chronic rejection scores and kinetics of alloAb elaboration were similar between groups. Conclusions: Delayed ICOS-Ig treatment with the reagent tested is probably ineffective in modulating pathogenic primate alloimmunity in this model. Abstract : Supplemental digital content is available in the text.